Recenzió: The Long Range Desert Group in North Africa - Edet, Blessing J. (Afrika Tanulmányok / Hungarian Journal of African Studies, 2025)
Blessing J. Edet a következő művet mutatta be: Brendan O’Carroll: The Long Range Desert Group in North Africa. Yorkshire: Pen & Sword Military, 2023. 256 pp.